Die juristische Person des evangelischen Kirchenrechts - Munsonius, Hendrik (Jus Ecclesiasticum, 2009)
Based on theological principles and the existing norms of church law, Hendrik Munsonius studies the prerequisites for and the consequences of the status of the incorporation through church law.